Effect of Hypopressive exercise in women with Pelvic Organ Prolapse - Parle, Jyoti; Shahmalak, Sana; Irkar, Divya (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aim: To study the effect of Hypopressive exercises to improve pelvic floor muscle strength in women with Pelvic Organ Prolapse.(grade 1and 2). Methods: This is an experimental study conducted on women of urban and rural areas of Kamothe and Kalamboli in India who presented with grade 1 and grade 2 Pelvic Organ Prolapse. 20 women (35 years and above) were recruited after taking their consent. The outcome measures assessed during pre and post evaluation were pelvic floor muscle strength as measured by modified oxford scale and perinometer whereas Pelvic Organ Prolapse symptoms by pelvic floor distress inventory scale-20. Intervention consisted of 6-weeks of Hypopressive exercises with a physiotherapist. The protocol consisted of three sessions weekly with progression in each week. Precautions to be taken during the study were explained to the participants each time. Results: Hypopressive exercises presented positive results with statistically significant difference in pre and post evaluation of outcome measures. Wilcoxon Signed Rank Test analysis reported p-value of 0.00 for modified oxford scale. For perinometer, p-value for peak, average, duration and gradient was 0.00, 0.00, 0.01 and 0.04 respectively. Pelvic Floor Distress Inventory Scale reported p-value of 0.00. Conclusion: Hypopressive exercises exhibited improvements in pelvic floor muscle strength and reducing the symptoms of Pelvic Organ Prolapse.